Формування здорової особистості дитини молодшого шкільного віку у процесі взаємодії школи і сім’ї - Семенова, Наталія; Репницька, Дар'я; Semenova, N.; Repnytska, D. (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті представлено психолого-педагогічні основи процесу формування здорової особистості дитини молодшого шкільного віку у процесі педагогічної взаємодії школи і сім’ї та дано оцінку його сучасному стану. Уточнено сутність понять „здорова особистість”, „взаємодія школи і сім’ї ”. Розроблено систему критеріїв і показників для діагностики рівнів сформованості здорової особистості молодшого школяра. Виявлено, що здорова особистість дитини молодшого шкільного віку поєднує знання про здоров’я (когнітивний компонент), прагнення бути здоровою (мотиваційний компонент) та здоров’ятворчу поведінку (діяльнісний компонент). Розроблено й апробовано експериментальну педагогічну технологію формування здорової особистості дитини молодшого шкільного віку у процесі взаємодії початкової школи і сім’ї.The article presents a psycho-pedagogical bases of the formation process of a healthy personality of the child of primary school age in the process of pedagogical interaction of school and family and an assessment of its current state The purpose of our article is to theoretically substantiate and experimentally tested to describe the pedagogical technology of formation of healthy personality of the child of primary school age in the process of interaction of school and family. The purpose of our article is to theoretically substantiate and experimentally tested to describe the pedagogical technology of formation of healthy personality of the child of primary school age in the process of interaction of school and family. Developed and tested an experimental pedagogical technology of formation of healthy personality of the child of primary school age in the elementary process of interaction of school and family. In the course of the study , proved an effective means to improve the formation of healthy personality of the child of primary school age in the process of interaction between schools and families is the pedagogical technology is a complex process health referral based on the interaction of all subjects of educational activities, the use of modern means of organization of education, aiming at personal development of younger pupils, which perceives health as the most basic value, has knowledge about the basics of health, committed to their search and own uses in its own activities.
The formation of healthy personality of the child of primary school in the process of interaction of school and family
Keywords: особистість; personality; взаємодія; формування особистості; розвиток; педагогічна технологія; interaction; formation of personality; development; educational technology